2011
DOI: 10.1111/j.1600-051x.2011.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingival changes during pregnancy: III. Impact of clinical, microbiological, immunological and socio‐demographic factors on gingival inflammation

Abstract: Bacterial challenge to the gingival tissues, both quantitatively (PlI) and qualitatively (harbouring P. gingivalis) appears to affect the level of gingival inflammation observed during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 83 publications
0
54
0
2
Order By: Relevance
“…Various studies have suggested a relationship between the progression of periodontitis and the expression levels of interleukin (IL)-1β, IL-6, tumor necrosis factor-alpha (TNF-α), and nitric oxide synthase (iNOS) in gingival crevicular fluid, gingival tissue, and blood with regard to both the protein and messenger RNA (mRNA) levels (Kendall et al, 2000;Lappin et al, 2000;Bickel et al, 2001;Hirose et al, 2001;Ejeil et al, 2003;Faizuddin et al, 2003;Figuero et al, 2010;Carrillo-de-Albornoz et al, 2012). However, only a few human studies have investigated the association between increased gingival inflammation during pregnancy and local immune system changes (Figuero et al, 2010;Carrillo-de-Albornoz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have suggested a relationship between the progression of periodontitis and the expression levels of interleukin (IL)-1β, IL-6, tumor necrosis factor-alpha (TNF-α), and nitric oxide synthase (iNOS) in gingival crevicular fluid, gingival tissue, and blood with regard to both the protein and messenger RNA (mRNA) levels (Kendall et al, 2000;Lappin et al, 2000;Bickel et al, 2001;Hirose et al, 2001;Ejeil et al, 2003;Faizuddin et al, 2003;Figuero et al, 2010;Carrillo-de-Albornoz et al, 2012). However, only a few human studies have investigated the association between increased gingival inflammation during pregnancy and local immune system changes (Figuero et al, 2010;Carrillo-de-Albornoz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few human studies have investigated the association between increased gingival inflammation during pregnancy and local immune system changes (Figuero et al, 2010;Carrillo-de-Albornoz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In an animal model, P. gingivalis-derived LPS infected pregnant mice exhibited reduced fetal weight and increased fetal resorption [244]. Another periodontal pathogen, T. denticola has also been associated with pregnancy complications and poor pregnancy outcome [221,222,243,245]. In a mouse model, it has been shown that T. denticola has an ability to disseminate to distant sites from the site of infection [246].…”
Section: Periodontal Diseases and Gdmmentioning
confidence: 99%
“…gingivalis [243]. In an animal model, P. gingivalis-derived LPS infected pregnant mice exhibited reduced fetal weight and increased fetal resorption [244].…”
Section: Periodontal Diseases and Gdmmentioning
confidence: 99%
See 1 more Smart Citation